Alteration of mucosa cell maturation pattern after exposure to different radiographic imaging methods - Ryna Dwi Yanuaryska; Sabrina Ceasy Anggraeni; Adhara Harvita Puspitasari; Rurie Ratna Shantiningsih; Munakhir Mudjosemedi; Rellyca Sola Gracea (Universidade Estadual de Campinas, 2021)
Aim: Dental imaging has been widely used for diagnosis in dentistry. However, dental X-ray may induce cytotoxicity leading to apoptosis in oral mucosa cells. The present study aimed to observe the maturation pattern of buccal and gingival cells after exposure to X-ray radiation from analog/digital panoramic scanning and cone beam computed tomography (CBCT). Methods: The research samples were 40 subjects who fulfilled the inclusion and exclusion criteria. The subjects were divided into the exposed (patients who received analog/digital panoramic radiography or CBCT) and controlled (patients who had no radiography examinations) groups, with 10 subjects in each group. Exfoliative cytology smears were obtained from buccal mucosa and gingiva before exposure (or on day 0 for the control group) and 10 days later. The cells were stained with the Papanicolaou method. Then, the superficial, intermediate, and parabasal cells were counted in each glass slide. Results: No significant differences (p > 0.05) were observed among all cell types between day 0 and 10 in the control group. Meanwhile, after exposure to three kinds of radiography examinations, the frequency of intermediate cells in buccal mucosa and gingiva increased (p < 0.05), but that of superficial cells decreased (p < 0.05) significantly. No significant difference was found in the parabasal cells (p > 0.05). The frequency differences between intermediate and superficial cells showed no significant difference between the buccal mucosa and gingiva. Conclusion: Analog/digital panoramic radiography and CBCT exposure can induce cytotoxicity by altering the maturation pattern of buccal mucosa cells and gingiva, so it is strongly recommended to only perform these procedures if necessary and avoid repeated exposure to the same patient.